Modification of the existing maximum residue levels for acrinathrin in peaches and sweet peppers. (5th July 2021) - ,; Bellisai, Giulia; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Ferreira, Lucien; Giner, German; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Cheminova A/S submitted a request to the competent national authority in Spain to modify the existing maximum residue levels (MRLs) for the active substance acrinathrin in peaches and sweet peppers. The data submitted in support of the request were found sufficient to derive MRL proposals for both crops. Adequate analytical methods for enforcement are available to control the residues of acrinathrin and its enantiomer in the plant matrices under consideration at the validated limit of quantification (LOQ) of 0.02 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐ and long‐term intake of residues resulting from the use of acrinathrin according to the reported agricultural practices is unlikely to present a risk to consumer health.